Using guanxi to conduct elite interviews in China - Li, Hongqin; Harvey, William S; Beaverstock, Jonathan V (Qualitative research : QR, 2023)
Drawing on two research projects in China, this article provides three contributions to the literature on elite interviews. First, we demonstrate how guanxi (informal, particularistic and personal connections) can help gain access and build trust with elite Chinese interviewees in a dynamic rather than a static manner. Second, we show the relational and ongoing process of elite interviewing, combining the sensemaking and sensegiving efforts of the interviewer and interviewee. We introduce the concept of sense-becoming to describe how researchers can develop a sense of strategy for future interviews. Third, we highlight the value of guanxi and co-positionality for the interviewer and interviewee to enhance interaction during interviews. We conclude by providing a heuristic for conceptualising the salience of guanxi and sensemaking for elite interviews in China.